2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944581
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties under heart failure conditions in a human ventricular cell: A modeling study

Abstract: Heart failure (HF) is one of the major diseases across the world. During HF the electrophysiology of the failing heart is remodeled, which renders the heart more susceptible to ventricular arrhythmias. In this study, we quantitatively analyze the effects of electrophysiological remodeling of the major currents of human ventricular myocytes on the dynamics of the failing heart. We develop a HF model using a modified version of a recently published model of the human ventricular action potential, the O'Hara-Vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…I Na reduction is well established in HF,4, 5, 6 but the possibility that sodium channel density and/or function is differentially remodeled within the various subcellular compartments (microdomains) of failing cardiomyocytes has not been previously addressed. Sodium channel clusters in various cardiomyocyte microdomains exhibit distinct current amplitudes and gating properties 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I Na reduction is well established in HF,4, 5, 6 but the possibility that sodium channel density and/or function is differentially remodeled within the various subcellular compartments (microdomains) of failing cardiomyocytes has not been previously addressed. Sodium channel clusters in various cardiomyocyte microdomains exhibit distinct current amplitudes and gating properties 9.…”
Section: Discussionmentioning
confidence: 99%
“…In failing hearts, reduced sodium current (I Na ) contributes to slowed conduction 4, 5, 6. Na V 1.5 is the major pore‐forming protein of the cardiac sodium channel and is responsible for the fast entry of sodium ions into cardiomyocytes, thereby underlying the upstroke of the action potential and mediating cardiac conduction.…”
mentioning
confidence: 99%
“…For chronic post-MI, ionic remodelling measured from minipigs 5 months post-MI with heart failure were used to generate Chronic BZ (affecting only the BZ) and Chronic RZ1 (also affecting the remote myocardium). Another type of remodelling, Chronic RZ2, was established based on multiple experimental data from failing human cardiomyocytes [45][46][47][48][49][50][51][52][53][54][55][56] . Furthermore, reduction of sodium current 46 and SERCA 47 , with enhanced CaMKII activity and slower calcium release 57,58 were also implemented in Chronic BZ, RZ1 and RZ2, as observed in human failing cardiomyocytes.…”
Section: Experimentally-informed Populations Of Post-mi Electromechan...mentioning
confidence: 99%
“…Newer electrophysiological models of ventricular myocytes have been recently developed based on particular experimental datasets, but their robustness in reproducing tissue, cellular, and sub-cellular behavior has been shown to be similar [10,17,30]. Furthermore, previous studies have shown that HF entails remodeling of cellular electrophysiology in the myocardium [52] and included it in cellular models [13,54]. In this study we used an undiseased human ventricular cell model as a reference, since we could not be sure about either to what extent ventricular cells had modified their electrophysiology for each patient or, considering they had modified it, whether their remodeling was homogeneous in both ventricles.…”
Section: Limitationsmentioning
confidence: 99%